Direct acid-catalysed mechanical depolymerisation of fibre sludge to reducing sugars using planetary milling. (March 2016) - Dong, Yue; Schneider, Laura; Hu, Tao; Jaakkola, Mari; Holm, Jana; Leveque, Jean Marc; Lassi, Ulla
Abstract: This study performed a direct solvent-free acid-catalysed mechanical depolymerisation of fibre sludge to reducing sugars which involves one step of acid milling in a planetary mill. The common reported 'solvent-free' mechanocatalytic depolymerisation of lignocellulose which includes 1) acid impregnation, 2) vacuum evaporation and 3) mechanocatalytic depolymerisation was also performed as a reference. The major converted monosaccharides were determined by capillary electrophoresis and the results of total reducing sugar (TRS) yields were carried out based on the 3, 5-dinitrosalicylic acid (DNS) method. The results showed that the TRS conversion of direct acid-catalysed mechanical depolymerisation of biomass is 35%, whereas, the commonly reported method yields 31% under the same milling conditions. In addition, the direct acid-catalysed mechanical depolymerisation simplifies the reaction procedures to one step and shortens the total reaction time. Moreover, the present study indicates that the frequency of the transferred energy which is caused by the collisions, acid concentration, milling time and moisture content of the sample are the major factors in influencing yield of converted TRS in acid-catalysed mechanical depolymerisation of fibre sludge. Highlights: Lignocellulose-based waste material, is converted to valuable products in a one-step process using planetary milling. Direct acid-catalysed mechanical depolymerisation is compared with common reported mechanocatalytic depolymerisation. Direct acid-catalysed mechanical depolymerisation affords higher yields of TRS than the impregnation-based method. The effect of two different sizes of grinding balls on TRS release has been determined.